Spectral analysis and abundances of the post-HB star HD 76431. Issue 4 (3rd November 2014) - Khalack, V.; Yameogo, B.; LeBlanc, F.; Fontaine, G.; Green, E.; Van Grootel, V.; Petit, P.
Abstract : HD 76431 is a slow rotating post-HB star that shows an underabundance of helium by 0.5 dex relative to the solar value. These observational facts suggest that atomic diffusion could be active in its atmosphere. We have used the MMT and Bok spectra to estimate the atmospheric parameters of the target star using the model atmospheres and synthetic spectra calculated with tlusty and synspec . The derived values of the effective temperature, surface gravity, and helium abundance are consistent with those obtained by Ramspeck et al. It appears that non-local thermodynamic equilibrium (NLTE) effects are not important for HD 76431. We have used Stokes I spectra from ESPaDOnS at CFHT to perform an abundance analysis and a search for observational evidence of vertical stratification of the abundance of certain elements. The results of our abundance analysis are in good agreement with previously published data with respect to average abundances. Our numerical simulations show that carbon and nitrogen reveal signatures of vertical abundance stratification in the atmosphere of HD 76431. It appears that the carbon abundance increases towards the deeper atmospheric layers. Nitrogen also shows a similar behaviour, but in deeper atmospheric layers we obtain a significant dispersion for the estimates of its abundance. To our knowledge, this is the first demonstration of vertical abundance stratification of metals in a post-HB star and up to now it is the hottest star to show such stratification features. We also report the detection of two Si iii and one Ti iii emission lines in the spectra of HD 76431 that were not detected in previous studies.